GENDER, FEMINIST AND QUEER STUDIES ([S.l.])
1 online resource
Keywords: Exploring scholarship, research, practice and activism on gender, feminist and queer studies, this edited collection examines, analyses and critiques the nature and causes of inequality, disadvantage and marginalisation faced by women, non-hegemonic and LGBTIQA+ identities who do not fit hegemonic notions of masculinity, femininity and heteronormativity. The chapters in this book critically analyse and challenge visible and invisible power relations, privilege and prejudice by problematising the artificial organisation of people into hierarchies that preference hegemonic masculinities, white and heteronormative identities. In questioning often unchallenged and legitimised inequality and disadvantage, this book locates itself in the juxtaposition where the lived experiences of individuals, activism, community participation, research and scholarship collide with mainstream, local, national and globalised culture and politics. Divided into four parts, this book provides a platform for interrogating how social change can occur in the current neoliberal political context of increasing conservatism.